1998
DOI: 10.3109/03639049809088526
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Characteristics of Injectable Poly(DL-Lactic Acid) Microspheres for Long-Acting Drug Delivery

Abstract: Poly(DL-lactic acid) (PLA) microspheres containing testosterone (T) were prepared by the solvent evaporation process to evaluate their physical properties such as size distribution, shape, drug content, in vivo controlled drug release, pharmacological influences on the prostate gland in castrated rats, and histopathological findings of tissues surrounding the implants. The in vivo release of T from PLA microspheres containing 30 mg of drug obtained with chloroform was continued over a 6-week period. This effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…However, studies were also reported where long-term complete degradation did not result in local complications [16,17,19]. For poly-DL-lactic acid in the formulation of microspheres for drug delivery complete degradation was already observed after 8 weeks [20]. So, various reactions can occur depending on the actual composition and production method of the poly-L-lactide (co)polymer.…”
Section: Introductionmentioning
confidence: 92%
“…However, studies were also reported where long-term complete degradation did not result in local complications [16,17,19]. For poly-DL-lactic acid in the formulation of microspheres for drug delivery complete degradation was already observed after 8 weeks [20]. So, various reactions can occur depending on the actual composition and production method of the poly-L-lactide (co)polymer.…”
Section: Introductionmentioning
confidence: 92%
“…Aliphatic polyesters have attracted wide attention due to their biodegradability, biocompatibility and processibility [2][3][4] and widely used in biomedical fields, such as absorbable bone screws, tissue engineering, surgical sutures and drug controlled release [5,6]. However, there are some problems for the use of these polymers in biomedical materials field, especially for cortical bone repair materials.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable polymers are used in traditional applications, such as surgical sutures [1,2] and matrices for drug delivery [3][4][5], and recently they became also the basis of more advanced biomedical systems. The field of Tissue Engineering, for example, capitalized on their degradability to create the temporary scaffolds required for cell growth and tissue regeneration [6][7][8].…”
Section: Introductionmentioning
confidence: 99%